Near-inertial ocean response to a typhoon on a continental slope in the Northern South China Sea - Zhang, Han; Wu, Renhao; Liu, Fu; Ni, Xiaobo; Tian, Di (Frontiers in Marine Science, 2024)
Typhoons are strong natural events that significantly influence the marine environment. In 2018, Typhoon Mangkhut traveled over a moored station with a depth ~1900 m on continental slope in the northern South China Sea, the near-inertial oceanic responses are studied based on the Regional Ocean Modeling System (ROMS) model simulation combined with observation data. Near-inertial currents after Mangkhut can be divided into three layers: near-circular polarized in upper ocean, across-slope polarized in deep ocean and along-slope polarized near the bottom, thickness of the three layers depend on the slope steepness. According to across-slope and along-slope intensified currents, the near-bottom vertical velocities and near-inertial energy were intensified at the moored station. The across-slope forth/back near-inertial flows brought cold/warm and salty/fresh water from deeper/shallower depth, increased vertical excursions of near-bottom temperature/salinity isolines and near-inertial available potential energy. The near-inertial barotropic across-slope currents were much greater than along-slope currents, with net cooling and salinity increase of the whole water column at the moored station. The core responses to Mangkhut were within 100 km around the station. The near-inertial kinetic energy generated both at sea surface and bottom slope, then propagated vertically into ocean interior and horizontally into the South China Sea basin as well as some topography-trapped waves propagated along the slope. This work enriches the understanding of air-sea interactions in coastal regions and the effect of ocean topography, especially after a typhoon.